Complaints, reviews and new perspectives. The school space according to Paulo Freire’s proposals and the contributions of expert theorists - Serra, María Florencia (Universidad Nacional del Litoral, 2022)
In this essay we propose exploring the dialogue between Paulo Freire’s proposals and the contributions made by social space theorists, addressing two research lines: the relationships between knowledge, education, and space, and the materiality of space in the school/educational field. Bearing this in mind, we inquire into the research works published by the Brazilian pedagogue in his last years after being exiled and the approaches proposed by Engels and Lefebvre. We hold that both works share some ideas in relation to the complaint about the false neutrality of the spatial aspect.